(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
Aim of research is to measure role of organizational Identification indicators in addressing causes of organizational crises in light of Corona pandemic, As intellectual framework of this research was formed through interaction of two variables (organizational Identification and crises). In order to understand and clarify this framework, indicators of organizational Identification have been adopted, represented by (loyalty, affiliation, similarity). As for dimensions of organizational crises, they were embodied in (deficiency in strategic thinking, lack of understanding of the organization’s environment, neglect of the innovation component, weak resources). This research sought to answer a number of questions by presenting intellectual implications of these variables. This is in addition to what was reached through the field side of the research in which it was relied on to design a questionnaire whose paragraphs fit nature of research sample, which was represented in a sample of managers and employees of private hospitals in Karbala governorate, namely (Al-Kafeel Specialized, Hajjah, Zain Al-Abidin(. Research came out with a set of conclusions, in light of which a number of recommendations were raised to hospitals of research community, One of most important conclusions reached by current research is that adoption of organizational Identification indicators effectively contributes to addressing organizational crises in management of hospitals in research community, especially in light of challenges imposed by Corona pandemic, Among most prominent recommendations is need to provide an organizational climate that encourages loyalty and belonging from employees at various levels towards hospital and its services provided, which is reflected in achievement of real and effective treatments in light of this pandemic.